The geology of the Welkom Goldfield with special reference to the "A", "B" and Beatrix Reefs - Dwyer, Gordon Bransby (Rhodes University, Faculty of Science, Department of Geology, 1993)
The first Witwatersrand gold deposits in the Orange Free State were discovered under younger cover rocks in the 1930's with the aid of drilling and geophysics. The Welkom gold deposits are found in the sedimentary rock sequences of the Central Rand Group, which represent unconformity bounded genetic packages. The structural configuration of the goldfield is one of a north to south trending synform that is split near it's axis by the De Bron and Homestead faults. The "B" Reef is a highly variable, erratically mineralised reef that lies on an unconformity at the base of the Spes Bona Formation. The "A" Reef Zone consists of several placers 1 including the "Reworked BPM" 1 the Witpan, the Uitsig, the Hanging Wall Grits and the Upper "A" Reef. The Beatrix Reef lies at the base of the Eldorado Formation on an unconformity surface overlying the Virginia Formation in the southern part of the Welkom Goldfield. The origin of gold in the Witwatersrand basin can be classified into the modified placer theory, the syngenetic theory and the epigenetic theory. From the distribution of basin edge unconformities it can be deduced that the Welkom fan depository was tectonically active on the western, southern and eastern margins during sedimentation. Palaeocurrent studies indicate that sediment was transported predominantly from the south and west. It is thought that the "B", "A" and Beatrix Reefs were all deposited in a braided stream environment. A multidisciplinary approach to ore evaluation of Witwatersrand deposits is considered to be the best method, where sedimentology, geostatistics and structural geology are used.
Keywords: Gold mines and mining -- South Africa -- Free State; Gold ores -- Geology -- South Africa